Management, Marketing and Promotion of Library Services Based on Statistics, Analyses and Evaluation - Kolderup Flaten, Trine (De Gruyter, 2006)
Rapid developments in information technology and media have resulted in increasingly diverse strategies for information retrieval by readers and users. The duty to cope with this phenomenon and to master the situation forms one of the biggest challenges facing libraries. In order to strengthen the awareness of the potential of tools for management and strategic planning, a two-day meeting was held under the auspices of IFLA's Management and Marketing Section in Bergen, Norway in August 2005. Managers of different types of libraries, researchers and educators from five continents shared their experiences with research methods, data collection, evaluation, performance measurement, best practice strategies and policies. This book contains their presentations in the form of full length articles.; ""For those of us who were unable to attend, this publication not only provides a valuable record, but also a useful and relevant set of papers around the conference theme.""Cathie Jilovsky in: Library Management 6+7/2007
English
Keywords: Libraries